External supportive moves in Yemeni Arabic as used by female speakers in the same gender and cross gender - Yahya Mohammed Al-Marrani (English, 2019)
This study investigates the types and frequency of supportive moves in Yemeni Arabic as used by female speakers in the same gender and cross-gender. The respondents of the study were 336 undergraduate students from Sana’a University, aged 20-23. All of the participants are relatively homogeneous in terms of their cultural background. The data were collected by using Discourse Completion Test (DCT). The analysis of the data is based on Blum-Kulka et al’s (1989) CCSARP (Cross-Cultural Speech Act Realization Project) coding scheme. The results showed that Yemeni females showed greater use of external supportive moves when interacting with females more than to males. Regarding the use of external supportive moves according to the direct head act of requests and indirect head of requests, in general, female respondents in F-F, F-M interactions have a great tendency to employ external supportive moves with the direct and indirect head act of requests. It seems that the use of external supportive moves in Yemeni Arabic with the indirect head act of requests is obligatory to mitigate and soften requests and make it polite request. In other words, it was observed that female respondents convey polite requests by using external supportive moves regardless of directness or indirectness.